Poems / by Henry Wadsworth Longfellow. - Longfellow, Henry Wadsworth, 1807-1882. (Tufts University. Tisch Library., 2016)
A new edition.; 1 online resource (2 volumes); Volume 1 of 2.; "In two volumes"--Title page.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.